2000
DOI: 10.1046/j.1526-4610.2000.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Valproate Sodium (Depacon) Aborts Migraine Rapidly: A Preliminary Report

Abstract: Intravenous valproate appears to be safe and effective for the acute treatment of migraine. Double-blind, placebo-controlled studies to further investigate the use of this agent in acute treatment of migraine attacks are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 10 publications
0
64
0
1
Order By: Relevance
“…Consistent with this view, several agonists at GABA receptors have been used as prophylactic antimigraine drugs. In this context, valproate (Cutrer et al 1997a;Shaygannejad et al 2006), baclofen in a small open study (Hering-Hanit 1999), and gabapentin (Di Trapani et al 2000) may prevent migraine attacks, while valproate has also been suggested to be effective in the acute treatment of migraine in another small open trial (Mathew et al 2000). Despite the above clinical evidence, it should be kept in mind that not all of the aforementioned compounds are selective in their action at GABA receptors, and the mechanisms involved in their antimigraine effect remain unclear.…”
Section: Gaba Receptorsmentioning
confidence: 99%
“…Consistent with this view, several agonists at GABA receptors have been used as prophylactic antimigraine drugs. In this context, valproate (Cutrer et al 1997a;Shaygannejad et al 2006), baclofen in a small open study (Hering-Hanit 1999), and gabapentin (Di Trapani et al 2000) may prevent migraine attacks, while valproate has also been suggested to be effective in the acute treatment of migraine in another small open trial (Mathew et al 2000). Despite the above clinical evidence, it should be kept in mind that not all of the aforementioned compounds are selective in their action at GABA receptors, and the mechanisms involved in their antimigraine effect remain unclear.…”
Section: Gaba Receptorsmentioning
confidence: 99%
“…Mathews and colleagues reported on a cohort of 61 patients treating 66 attacks of acute migraine with rapid infusion of 300 mg of IV sodium valproate. 105 A reduction of moderate to severe pain to mild or no pain was achieved in 37 of 66 attacks at 30 minutes. An additional 11 attacks had a greater than 50% reduction of pain intensity.…”
Section: Intravenous Sodium Valproatementioning
confidence: 97%
“…Furthermore, the effect of valproate is mimicked by the GABA-A agonist (muscimol) but not by the GABA-B agonist (baclofen), suggesting a GABA-A-mediated mechanism. Although valproate and divalproex are more often used in the preventive treatment of migraine, valproate also seems effective for acute treatment [ 33 ]. It is established that the substantia gelatinosa of the spinal cord receives descending 5-HT fi bers from the rostroventral medulla, and these fi bers connect with spinothalamic neurons [ 34 , 35 ].…”
Section: Valproate and Divalproexmentioning
confidence: 99%